THE ASSOCIATION BETWEEN POOR GLYCAEMIC CONTROL (HBA1C LEVELS ≥ 7%) AND HIGHER INCIDENCE OF DIABETIC RETINOPATHY IN SMALL GROUP OF TYPE 2 DIABETES MELLITUS PATIENTS ATTENDING MAHATMA GANDHI MEMORIAL GOVERNMENT HOSPITAL, TRICHY - Sigamani, Vijayalakshmi; Devi Kanagaraj, Nirmala; Kuppuswamy Rajagantham, Vijayabharathi (Journal of evolution of medical and dental sciences, 2017)
BACKGROUND Diabetes mellitus is prevalent worldwide. Lot of research work has been done and published on Diabetes Mellitus and its long-term complications. But studies related to the control of diabetes mellitus and its duration with respect to the onset and severity of its microvascular complications are not widely conducted in India. This study was taken up to study the causal relationship between the control (based on [HbA.sub.1c] levels; [HbA.sub.1c] [greater than or equal to] 7% is considered as poor glycaemic control) and the onset of complications. MATERIALS AND METHODS It is a case-control study with a total of 60 subjects. Cases were Type 2 DM Patients with Diabetic Retinopathy (DR) and Controls were Type 2 DM without signs suggestive of DR. Subjects were selected based on self-answered research questionnaire and then a careful fundal examination. A total of 31 cases and 29 control subjects were included in this study. Poor Glycaemic Control ([HbA.sub.1c] levels [greater than or equal to] 7%) was taken as Exposure Factor. HbA1C levels was assayed in every subject using HemoCue Analyser using Column Cartridges (Boronate Affinity Chromatography). After collecting the data, the statistical analysis was done by calculating the Odd's Ratio using MedCalc easy to use statistical software. RESULTS Out of the 31 cases, poor glycaemic control was present in 25 subjects and absent in 6 subjects. Out of the 29 Controls, poor glycaemic control was present in 18 and absent in 11. The significance of association between Poor Glycaemic Control and DR was assessed by calculation of Odd's ratio (using MedCalc Easy-to-use Statistical Software) at 95% Confidence Interval and with a pvalue 0.05, the Confidence levels (lower and higher values) was got and statistical interpretation done. Odds ratio was 2.75 which shows significant association between poor Glycaemic control of Diabetes (high [HbA.sub.1c] levels) and presence of complications (Diabetic Retinopathy). CONCLUSION It is concluded that there is a strong association between poor Glycaemic Control ([HbA.sub.1c] [greater than or equal to] 7%) and higher incidence of Diabetic Retinopathy. KEYWORDS Diabetes Mellitus, Diabetic Retinopathy, HbA1c.